TYPOLOGY OF INTERIOR ARCHITECTURE FOR TRADITIONAL MOSQUES IN PENINSULAR MALAYSIA FROM 1700 – 1900 AD (Tipologi Seni Bina Masjid-Masjid Tradisional di Semenanjung Malaysia dari 1700 – 1900 Masihi) - Ahmad, Azizul Azli; Ali@Mat Zin, Aizan; Arbi, Ezrin (Journal of Al-Tamaddun, 2013)
This paper is based on an analysis of typological plan and main structures in several traditional mosques in Peninsular Malaysia. Emphasis is given on main prayer area and the main structure which supports the mosques? roof system. Traditional or early mosque was identified by its multi-tiered pyramidal roofs. Hence, objective of this study is to identify the forms and categories of the mosque on the building structure. Nowadays, the unique characteristic of this mosque has survived the test of time and can still be viewed on various traditional mosques. This exceptional roof system has put the mosques in its own exclusive circle, different from the rest of other mosques in the Islamic world. Thus, this study involves an analysis of 13 mosques which were constructed between 1700 to 1900 AD in Peninsular Malaysia. Finding of this study shows that the main prayer area is square-shaped, supported by four central columns in the middle of it. The four main structures which raised the roof system had influenced the shape and architecture of the multi-tiered pyramidal roofs of mosques in Peninsular Malaysia.